Antimicrobial resistance of rapidly growing mycobacteria isolated from companion animals in Taiwan - Chen, Shu-Wen; Chen, Ter-Hsin; Huang, Wei-Hsiang; Hou, Chia-Chun; Lin, Chen-Jou; Chang, Yi-Fu; Wu, Hsin-Yi; Wu, Ying-Chen (Microbiology spectrum, 2025)
Rapidly growing mycobacteria (RGM) are opportunistic pathogens in both humans and animals, posing significant challenges in diagnosis and treatment. The variable antimicrobial resistance profiles and inducible macrolide resistance complicate the design of multidrug regimens. Research on RGM infections in dogs and cats is limited, particularly studies examining inducible macrolide resistance. This study identified Mycobacterium abscessus complex and M. fortuitum complex as the predominant species in dogs and cats in Taiwan. Both species exhibited poor susceptibility to many antibiotics. M. fortuitum demonstrated lower minimum inhibitory concentration (MIC) values for fluoroquinolones and higher MIC values for clarithromycin, whereas M. abscessus complex showed the reverse pattern. Inducible macrolide resistance was present in our RGM isolates, and the detection of the erm genes provided a reliable prediction. These results support clinical diagnosis and the formulation of multidrug treatment regimens for RGM infections in dogs and cats.